2018
DOI: 10.1159/000490852
|View full text |Cite
|
Sign up to set email alerts
|

Transferability and Sustainability of Motor-Cognitive Dual-Task Training in Patients with Dementia: A Randomized Controlled Trial

Abstract: Background: Specific dual-task (DT) training is effective to improve DT performance in trained tasks in patients with dementia (PwD). However, it remains an open research question whether successfully trained DTs show a transfer effect to untrained DT performances. Objective: To examine transfer effects and the sustainability of a specific DT training in PwD. Methods: One hundred and five patients with mild-to-moderate dementia (Mini-Mental State Examination: 21.9 ± 2.8 points) participated in a 10-week random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 52 publications
(138 reference statements)
2
37
0
1
Order By: Relevance
“…Most of the studies identified, quantified as outcome measures the gait performance of in DT [23][24][25][26][27][28] , and many in turn measured static and dynamic equilibrium with a variety of scales or measurements, including support on one foot 6,27,29 , Time Up and Go (TUG) 25,27,29,30 and the Berg Balance Scale (BBS), which was used by three studies 26,29,30 . Other scales, such as the Balance Evaluation System Test (BEST) 31 and the Tinetti scale 32 , were used to a lesser extent.…”
Section: Conceptual Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies identified, quantified as outcome measures the gait performance of in DT [23][24][25][26][27][28] , and many in turn measured static and dynamic equilibrium with a variety of scales or measurements, including support on one foot 6,27,29 , Time Up and Go (TUG) 25,27,29,30 and the Berg Balance Scale (BBS), which was used by three studies 26,29,30 . Other scales, such as the Balance Evaluation System Test (BEST) 31 and the Tinetti scale 32 , were used to a lesser extent.…”
Section: Conceptual Descriptionmentioning
confidence: 99%
“…The interventions were developed in diverse settings, in community dwelling people 27,33 and people living in care homes 24,32 . Concerning age, only three studies accepted people of average adult age, all of them adults with neurological 23,31 and skeletal 29 pathologies, while the rest of the studies had only an older adult population.…”
Section: Characteristics Of the Scope And Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…More studies are needed on this subject. While only orthopedic and neurological problems were the majority in the studies, healthy elderly individuals were also included in our study (33). In our study, the agility and dynamic balance performances of the patients who received single and double task training showed an improvement compared to the TUGT.…”
Section: Testingmentioning
confidence: 88%
“…There are some contradictions in evaluating the results obtained due to the sample size (n<30) in some studies showing a shortcoming of these studies. Therefore, the sample size was decided to be 60 to prevent these contradictions (33).…”
Section: Discussionmentioning
confidence: 99%